Simple and sensitive electrokinetic supercharging in capillary electrophoresis for online preconcentration and separation of secbumeton in water samples - Soeung, Rasmey; Nadhiratul-Farihin Semail,; Wan Adnan Wan Omar,; Nur Nadhirah Mohamad Zain,; Mazidatulakmam Miskam,; Yong, Foo Wong; Aemi Syazwani Abdul Keyon,; Muggundha Raoov Ramachandran,; Sazlinda Kamaruzaman,; Noorfatimah Yahaya, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study describes an electrokinetic supercharging for online preconcentration capillary electrophoresis (CE) technique of secbumeton in water samples. Important CE separation and preconcentration conditions, such as concentration and pH of the background electrolyte, applied voltage and ultraviolet wavelength, type and injection time of the terminating electrolyte, and injection time of the leading electrolyte and sample were investigated and optimized. The optimum conditions involved hydrodynamic injection of leading electrolyte (100 mM sodium chloride, 30 s, 50 mbar), electrokinetic injection of the sample as high as 250 s (at +7 kV voltage), and hydrodynamic injection of terminating electrolyte (100 mM Tris buffer, 40 s, 50 mbar). This strategy enhanced secbumeton detection sensitivity up to 3847-fold and 2267-fold when compared with hydrodynamic and electrokinetic injection, respectively, providing a limit of detection as low as 0.03 µg L–1 with good repeatability (relative standard deviation < 4%, n = 5). Wide linear range (0.1–500 µg L–1) with good linearity (R2 = 0.9997) was obtained. The limit of detection was adequate for the analysis of secbumeton in water samples with concentrations lower than its maximum residual limit (0.1 µg L–1). The developed method was applied to environmental water samples, and recoveries were between 85.7 and 105.6%.